Gestión de liderazgo y la cultura organizacional de los comisariatos del cantón la maná, 2021. - Fonseca Molina, Marco Bryan (2022)
The organizational culture is an important aspect that is often overlooked or misunderstood by leaders. Understanding what culture represents and what it constitutes in the different levels within an organization's culture, as well as recognizing the difference between positive and toxic cultures, are the key for a healthy organization. Ideally, it means stability for the organization; since it allows its permanence to the organization and encourages it to look towards the future. Therefore, the present project is focused on determining the management leadership within the organizational culture of supermarkets of La Maná canton. To comply with the objectives a bibliographic, field and non-experimental study have been stated; given that the information presented was compiled from a search carried out in books, magazines, university repositories, as well as directly from the events scene. The study had a population of 81 people conformed of workers, managers, or owners of 10 supermarkets in the canton of La Maná, to whom interviews and surveys were applied. The results show that the supermarket of La Maná canton have a weak leadership management which has an effect on the organizational culture, with the workers being the principal element of the statistical data found, therefore the companies must teach the managers how to support their employees instead of simply being the gatekeeper of their inner careers. Since an organization will be effective only when the culture is supported by a suitable business strategy and an appropriate structure for both the business and the desired culture.